Arsenic sequestration in pyrite and greigite in the buried peat of As-contaminated aquifers. (1st September 2020) - Wang, H.Y.; Byrne, J.M.; Perez, J.P.H.; Thomas, A.N.; Göttlicher, J.; Höfer, H.E.; Mayanna, S.; Kontny, A.; Kappler, A.; Guo, H.M.; Benning, L.G.; Norra, S.
Abstract: Detrital peat (organic carbon-enriched deposit) with high arsenic (As) content is widely distributed in sediments where groundwater As contamination exists. Iron sulfides often persist in these sediments under anoxic conditions. However, the mechanisms and pathways of formation of iron sulfides and its potential contribution in controlling As mobility are still poorly understood. In this study, we examined three As-contaminated peat sediments from the Hetao Basin in China to gain better understanding of the complex interplay between iron sulfides formation and As mobility. We employed high-resolution spectroscopic techniques, including X-ray absorption spectroscopy and 57 Fe Mössbauer spectroscopy, coupled with electron microscopy to determine the speciation of iron sulfides and the associated As in the peat sediments. Pyrite (FeS2 ) and metastable greigite (Fe3 S4 ) persisted in peat as end-members of S and Fe diagenetic pathways. The Fe-rich phyllosilicates and decaying plant tissues provided the ideal micro-environments for pyrite and greigite nucleation. Pyrite formation most likely occurred via the polysulfides pathway in the surface water-sediments interface during early diagenetic process, while the relative enrichment of reactive Fe compared to sulfide possibly inhibited the transformation of greigite to pyrite in such Fe-rich sediments. Our results revealed that the peat sediments could act as a stable sink for As immobilization under steady groundwater anoxic conditions, with As content up to 250 mg/kg and large proportions (40 to 60 wt.% As) sequestered in pyrite and greigite. Pyrite crystallites had up to 1 wt.% As content through the replacement of the S -I sites. Greigite crystallites had a relatively constant As content ranging from ∼500 to ∼1400 mg/kg. Instead of being adsorbed or structurally incorporated, arsenic formed distinct arsenic sulfide phase in the greigite-enriched sediments, which was analogous to realgar. The transfer of As from iron sulfides to ferrihydrite temporarily retarded As release into groundwater under slightly oxic groundwater conditions. However, the reductive dissolution of ferrihydrite and potential subsequent As re-release could be a source of As in groundwater under disturbed redox conditions.